2022
DOI: 10.3390/nu14030535
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of the Prevalence of Cobalamin Deficiency and Vitamin B12 Supplementation Habits among Vegetarian and Vegan Children in the Czech Republic

Abstract: Vegetarian (VG) and vegan (VN) diets in childhood are of growing interest due to their perceived health and environmental benefits. Concerns remain due to the possible disruption of healthy growth and development of children because of the scarcity of evidence-based studies. Among the nutrients of special concern is vitamin B12. Therefore, the Czech Vegan Children Study (CAROTS) decided to examine the relationship between B12 metabolism parameters and B12 intake through diet and supplementation. We analyzed la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
0
22
0
1
Order By: Relevance
“…While the knowledge about the necessity of vitamin B12 supplementation seems to be well known among vegans (40) we do not have any information about their iodine status. Therefore, the reason to run this study was a description of iodine saturation, intake, and supplement use in Czech children consuming plant-based diets, and to describe if these children are at possible risk of iodine de ciency, as described reported from cross-sectional studies in adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the knowledge about the necessity of vitamin B12 supplementation seems to be well known among vegans (40) we do not have any information about their iodine status. Therefore, the reason to run this study was a description of iodine saturation, intake, and supplement use in Czech children consuming plant-based diets, and to describe if these children are at possible risk of iodine de ciency, as described reported from cross-sectional studies in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike pregnant and lactating women, no attention has been paid to this group so far by public health authorities. Considering the increasing prevalence of plant-based diets, especially in the paediatric population, there is an urgent need for proper guidelines accessible for health professionals for assessing iodine de ciency using suitable markers (40), and the prevention of iodine de ciency via iodine supplementation should be enforced. In this regard, the present research should stimulate an evidence-based discussion concerning medical guidelines and recommendations with a speci c focus on the paediatric population consuming plantbased diet in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently taken supplements were B12 (82%), vit D (80%), omega-3 (51%), and iron (50%). B12 supplementation was similarly assessed for German vegans (82%) 2 and Czech children (86%) 32 . In a survey of healthcare professionals who were physically present at an international conference on plant-based nutrition, 98% of vegans self-reported supplementing B12 33 .…”
Section: Discussionmentioning
confidence: 99%
“…124 Studies on ASD have found that alterations in the methylation cycle commonly cause a buildup of homocysteine, which can harm neurons and interfere with the production of proteins and neurotransmitters through its metabolic products it produces. 125 In the presence of VB12 deficiency, tetrahydrofolate cannot be converted to folic acid, and homocysteine levels are elevated. This finding was also confirmed by Guo et al through a meta-analysis of 1641 studies, where serum levels of Hcy were significantly higher in patients with ASD compared to healthy controls (Hedges's g = 0.56, 95% CI = 0.36 to 0.76, P < 0.001).…”
Section: Vitamin Bmentioning
confidence: 99%